The questionnaire assessments provoking situation of social-comparison jealousy - Fourmanov, Igor A.; Lepeshko, Kseniya V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article presents the psychometric rationale of questionnaire assessments provoking situation of social-comparison jealousy. The data for determining the reliability by criterions of stability and internal coordination of questionnaire; by criterions of internal validity and ecological validity of questionnaire; by criterions of separate points discrimination of questionnaire are cited.